Coconut embryo In Vitro culture: Proceedings of the first workshop on embryo culture, 27-31 October 1997, Banao, Guinobatan, Albay, Philippines - Batugal, P.A.; Engelmann, F. (1998)
Efficient use of coconut genetic resources has been hampered by difficulties in collecting and exchanging germplasm. Because of the size of the nuts and the fact that the nuts have no dormancy period, collecting of coconut seednuts is costly. This method of coconut collecting is expensive, and restricts the numbers of samples, and hence the genetic diversity that can be collected. Germplasm exchange is also difficult due to increased risk of pest and disease movement, and the expense in transporting whole nuts. The embryo (and not the whole nut) is all that is needed to produce a whole plant. Thus collecting, and exchange of coconut embryos using in vitro methods is potentially cheaper, more effective, and safer. Simple in vitro techniques for field collecting and embryo culture have been developed and implemented by as yet, a very limited number of countries. Those laboratories and countries that have developed in vitro techniques, have found different protocols that worked best. There have been difficulties in extending and implementing these techniques, especially in weaning or hardening of in vitro plantlets, prior to successful transplanting. In an attempt to explore and overcome these problems, a workshop on coconut embryo in vitro culture was conducted on 27-31 October 1997. The workshop was hosted by the Albay Research Center of the Philippine Coconut Authority and attended by representatives of research laboratories in both developed and developing countries where the most advanced coconut embryo culture work is being conducted. The workshop aimed at presenting participants' latest research results with coconut embryo culture and acclimatization of resulting plantlets, identifying bottlenecks and areas for improvement, developing a research agenda for the next two years to solve current difficulties, and producing an optimized in vitro culture protocol which can easily be applied by non-specialists.